Study of carbonic acids of roots Comarum palustre L. - Rudnyk, A.; Khvorost, O.; Fedchenkova, Yu.; Skrebtsova, K.; Duchenko, M.; Рудник, Анна Михайлівна; Хворост, О.; Федченкова, Ю.; Скребцова, К.; Дученко, М. (My University, 2025)
Actuality. According to the literature, the underground organs of Comarum palustre L. contain organic acids, and there is no information about their component composition. The purpose of the study is to study the component composition of organic acids in the roots of Comarum palustre L. and determine the quantitative content of the sum of organic acids in 7 series of raw materials present on the pharmaceutical market of Ukraine. Material and methods. Plant raw materials for research were purchased in the spring of 2024 in online markets of Ukraine specializing in the sale of medicinal plant raw materials: series 1 – “Chlorophytum”, series 2 – “Sednivski travy”, series 3 – “Svit trav”, series 4 – TM “Organic herbs”, series 5 – “PbayMarket”, series 6 – “Narod pharma”, series 7 – “Dary Karpat”. The component composition of organic acids was studied by gas chromatography-mass spectrometry. The quantitative content of the sum of organic acids was determined by the method of the monograph of the State Pharmacopoeia of Ukraine 2.1 “Rosehips FruitsN”. Research results. In the roots of Comarum palustre, for the first time, the presence of 6 dicarboxylic acids was established by the method of chromatography-mass spectrometry and the quantitative content of each of them was determined. Their total content was 1462.49 μg\g. Three carboxylic acids were dominant in content: levulinic (almost 47% of the total content of identified acids), citric and malic acids (28.49% and 15.41%, respectively). For the first time, in 7 batches of raw materials purchased in Ukraine, the quantitative content of the sum of organic acids in terms of malic acid was determined in the roots of Comarum palustre, using the modified method of the monograph of the State Pharmacopoeia of Ukraine 2.1 “Rosehips FruitsN”. The quantitative content of organic acids varies more than 1.2 times – from 1.98% (series 1) to 2.41% (series 6). The validation characteristics of the method were established for the first time and tested on five batches of raw materials. Conclusions. For the first time, the component composition of organic acids was established in the roots of Comarum palustre by the method of gas chromatography-mass spectrometry. For the first time, the content of organic acids in 7 series of Comarum palustre roots purchased in specialized marketplaces of Ukraine was determined. The obtained data will be used in further pharmacognostic research of Comarum palustre roots. Актуальність. За даними літератури, підземні органи Comarum palustre L. містять органічні кислоти, а інформація про їх компонентний склад відсутня. Мета дослідження. Вивчити компонентний склад органічних у коренях Comarum palustre L. та визначити кількісний вміст суми органічних кислот у 7 серіях сировини, яка присутня на фармацевтичному ринку України. Матеріали та методи. Рослинну сировину для досліджень було придбано навесні 2024 року в internet-маркетах України, які спеціалізуються на продажу лікарської рослинної сировини: серія 1 – «Хлорофітум», серія 2 – «Седнівські трави», серія 3 – «Світ трав», серія 4 – ТМ Organic herbs, серія 5 – PbayMarket, серія 6 – «Народ фарма», серія 7 – «Дари Карпат». Компонентний склад органічних кислот вивчали методом газової хромато-мас-спектрометрії. Кількісний вміст суми органічних кислот визначали за методикою монографії ДФУ 2.1 «Шипшини плодиN». Результати дослідження. У коренях Comarum palustre вперше методом хромато-мас-спектрометрії встановлено присутність 6 дикарбонових кислот та визначено кількісний вміст кожної з них. Їх загальний вміст становив 1462,49 мкг/г. Домінуючими за вмістом виявилися три карбонові кислоти: левулінова (майже 47% від загального вмісту ідентифікованих кислот), лимонна та яблучна кислоти (28,49% та 15,41% відповідно). Уперше в 7 серіях придбаної в Україні сировини, коренях Comarum palustre, визначено кількісний вміст суми оранічних кислот у перерахунку на яблучну за модифікованою методикою монографії ДФУ 2.1 «Шипшини плодиN». Кількісний вміст органічних кислот коливається більше ніж у 1,2 раза – від 1,98% (серія 1) до 2,41% (серія 6). Уперше встановлено валідаційні характеристики методики й апробовано її на п’яти серіях сировини. Висновки. Уперше методом газової хромато-мас-спектрометрії в коренях Comarum palustre L. встановлено компонентний склад органічних кислот. Уперше визначено вміст органічних кислот 7 серій коренів Comarum palustre, придбаних у спеціалізованих маркетплейсах України. Отримані дані будуть використані в подальшому фармакогностичному дослідженні коренів Comarum palustre.
Дослідження карбонових кислот коренів Comarum palustre L.
Keywords: Comarum palustre L.; roots; series; organic acids; component composition; quantitative content; gas chromatographymass spectrometry; корені; серії; органічні кислоти; компонентний склад; кількісний вміст; газова хромато-мас-спектрометрія